2011
DOI: 10.1111/j.1742-481x.2011.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure ulcer prevention in Australia: the role of the nurse practitioner in changing practice and saving lives

Abstract: This paper reports on a successful nurse practitioner-led Pressure Ulcer Prevention Program (PUPP), established with members from nursing, allied health and senior management, within a regional area health service in Australia. The aims of PUPP were to quantify the prevalence of pressure ulcers within the health organisation, evaluate the policy compliances, identify cost effectiveness by implementing appropriate pressure redistributing surfaces and raise awareness of pressure ulcer prevention amongst all leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 4 publications
0
34
0
2
Order By: Relevance
“…Most of the studies on PIs reported prevalence. Some measured the prevalence of PIs in acute health care facilities (eg, hospitals) . Prevalence ranged from 0.2% to 29.6% in hospital settings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies on PIs reported prevalence. Some measured the prevalence of PIs in acute health care facilities (eg, hospitals) . Prevalence ranged from 0.2% to 29.6% in hospital settings.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the studies that measured PI prevalence in health care facilities reported on rates of health care‐, versus community‐, acquired PIs . One study found the prevalence of PIs on admission to hospital to be 4.9%, versus prevalence at discharge of 5.7% .…”
Section: Resultsmentioning
confidence: 99%
“…Initiatives such as the Crystal Model reinforce the shared responsibilities of health professionals and development of collaborative goals promoted within the literature . The promotion of collaborative goals encourages the adoption of PI prevention and management strategies by all members within an MDT . Ashby et al .…”
Section: Role and Identity Of Health Professionalsmentioning
confidence: 99%
“…Hastaya iki saatte bir yatakta yön değiştirilmesi, basınç giderici özel yatakların kullanımı ile basıncın tüm yüzeye eşit dağıtılması, çarşafların temiz ve ütülü olması, enfeksiyonların kontrolü, uygun beslenmenin sağlanması, hipoalbüminemi, kan şekeri yük-sekliği, anemi, dolaşım bozukluğu gibi durumların tedavisi ile bası ülserlerinin oluşumu önlenebilir [12]. Bası ülserlerinin önlenmesinde en büyük rol bu alanda özel eğitim almış hemşirelerindir [13].…”
Section: Yatağa Bağımlı Hastalarunclassified